2005
DOI: 10.1038/sj.cdd.4401661
|View full text |Cite
|
Sign up to set email alerts
|

Cells die with increased cytosolic ATP during apoptosis: a bioluminescence study with intracellular luciferase

Abstract: Apoptosis is a distinct form of cell death, which requires energy. Here, we made real-time continuous measurements of the cytosolic ATP level throughout the apoptotic process in intact HeLa, PC12 and U937 cells transfected with the firefly luciferase gene. Apoptotic stimuli (staurosporine (STS), tumor necrosis factor a (TNFa), etoposide) induced significant elevation of the cytosolic ATP level. The cytosolic ATP level remained at a higher level than in the control for up to 6 h during which activation of caspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
220
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(243 citation statements)
references
References 35 publications
19
220
4
Order By: Relevance
“…After 96 h, the first signs of apoptosis were observed, the cells were highly active and have maintained their elevated mitochondrial activity. This is consistent with the literature, in which it is known that the apoptotic process demands high energy for its development (Eguchi et al, 1997;Zamaraeva et al, 2005). Recent studies showed that cells undergoing apoptosis show the same or even better energy status as long as the cells maintained a highly active metabolism (such as various biosynthesis processes including lipid biosynthesis, DNA fragmentation and so on; Budd et al, 2000;Zamaraeva et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…After 96 h, the first signs of apoptosis were observed, the cells were highly active and have maintained their elevated mitochondrial activity. This is consistent with the literature, in which it is known that the apoptotic process demands high energy for its development (Eguchi et al, 1997;Zamaraeva et al, 2005). Recent studies showed that cells undergoing apoptosis show the same or even better energy status as long as the cells maintained a highly active metabolism (such as various biosynthesis processes including lipid biosynthesis, DNA fragmentation and so on; Budd et al, 2000;Zamaraeva et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…17 Additionally, a different study asserted that an elevation in cytosolic ATP, and thus a decline in the ADP/ATP ratio even below levels detected in healthy cells, was necessary for propagation of apoptosis. 18 Therefore, there is even significant disagreement in the literature concerning the meaning of the ADP/ATP ratio as it relates to the quality of a cellular preparation; both high and low ADP/ATP ratios have been associated with increased cell death. It has been hypothesized that the increase in cytosolic ATP in cells undergoing apoptosis will not be sustained and that ATP as well as ADP will be depleted shortly after the execution phase of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Several reports showed that intracellular ATP levels remain unchanged or even elevated for a short time in STP or in etoposide-induced apoptosis, and then gradually decrease until the very end of the death process. [35][36][37] We first demonstrated that this phenomenon occurs in GzmB-induced apoptosis (Figure 8a). However, we found that, after GzmF treatment, intracellular ATP diminishes at an early stage, which is much earlier than cyt c release.…”
Section: Discussionmentioning
confidence: 99%